2022
DOI: 10.1016/j.psj.2021.101607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of freezing on the quality of breast meat from broilers affected by White Striping myopathy

Abstract: The aim of this study was to evaluate possible changes in the quality of chicken breast meat containing white stripes during freezing for 12 mo. Samples of Pectoralis major muscle from male Cobb 500 broilers containing white stripes in moderate and severe degrees were used, as well as samples from a control group (normal – absence of myopathies). Part of the samples (n = 60; n = 20 for each severity degree) were analyzed on the day of collection (beginning) and the rest (n = 240) was frozen (−20°C) for up to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
(75 reference statements)
3
5
0
Order By: Relevance
“…In general, there was a reduction ( P < 0.05) in mineral concentrations in meat as storage time increased for Ca (0.288 g/kg), P (10.7 g/kg), K (12.51 g/kg), and Mg (1 g/kg) at 12 mo when compared to time 0 (0.488 g/kg; 10.92 g/kg; 13.38 g/kg; 1.06 g/kg for Ca, P, K, and Mg, respectively), mainly due to the action of ice crystals on the cell membrane, which decreased the WHC of the meat and favoring losses of soluble material (such as minerals) ( Petracci et al, 2015 ). Results similar to those presented by Pereira et al (2022) , who evaluated the effect of freezing chicken breasts affected by white stripping myopathy.…”
Section: Resultssupporting
confidence: 80%
“…In general, there was a reduction ( P < 0.05) in mineral concentrations in meat as storage time increased for Ca (0.288 g/kg), P (10.7 g/kg), K (12.51 g/kg), and Mg (1 g/kg) at 12 mo when compared to time 0 (0.488 g/kg; 10.92 g/kg; 13.38 g/kg; 1.06 g/kg for Ca, P, K, and Mg, respectively), mainly due to the action of ice crystals on the cell membrane, which decreased the WHC of the meat and favoring losses of soluble material (such as minerals) ( Petracci et al, 2015 ). Results similar to those presented by Pereira et al (2022) , who evaluated the effect of freezing chicken breasts affected by white stripping myopathy.…”
Section: Resultssupporting
confidence: 80%
“…The moisture content in meat is critical as it helps maintain the meat's juiciness and tenderness. However, improper handling during the meat thawing process can lead to the loss of moisture, resulting in a dry meat with a changed texture that affects the overall eating experience ( Pereira et al, 2022 ). Moreover, some water-soluble vitamins and minerals may be leached out during the thawing process, hence diminishing the nutritional value of the meat.…”
Section: Discussionmentioning
confidence: 99%
“… Ali et al (2015) , investigating several cycles of freezing and thawing on the quality of broiler breasts, identified an increased lipid and protein oxidation, alongside reduced color stability and pH. Pereira et al (2022) worked with the evaluation of chicken breasts affected with WS frozen for 12 mo and analyzed possible changes in their quality, however the analyzed parameters were different from those listed in this study. In any case, they concluded that myopathy significantly affects meat quality both sensorially and physically and chemically.…”
Section: Introductionmentioning
confidence: 94%
“…However, these advances are associated with the occurrence of myopathies in broiler chickens, studies suggest that there is a multifactorial combination of genetic, nutritional, environmental and management variables that affect the development of myopathies ( Che et al, 2022 ). Amongst them, white striping ( WS) myopathy is easily recognized by the occurrence of white striations on the surface of the breast, which may lead to a product rejection by the consumers ( Carvalho et al, 2021a ; Pereira et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%